The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/mcb.22.3.935-945.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor Nor-1 Is Essential for Proliferation of the Semicircular Canals of the Mouse Inner Ear

Abstract: Nor-1 belongs to the nur subfamily of nuclear receptor transcription factors. The precise role of Nor-1 in mammalian development has not been established. However, recent studies indicate a function for this transcription factor in oncogenesis and apoptosis. To examine the spatiotemporal expression pattern of Nor-1 and the developmental and physiological consequences of Nor-1 ablation, Nor-1-null mice were generated by insertion of the lacZ gene into the Nor-1 genomic locus. Disruption of the Nor-1 gene result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 43 publications
4
75
1
Order By: Relevance
“…Transgenic expression of a dominant negative Nur77 protein, which can inhibit both Nur77 and Nor-1, does antagonize negative selection. 75,76 Therefore, it has been hypothesized that there may be redundancies between the family members. How Nur77 can induce apoptosis is still unclear, but one proposed mechanism is that upon TCR stimulation Nur77 is translocated from the nucleus to the mitochondria where it interacts with BCL-2 inducing a conformational change that converts BCL-2 into a proapoptotic molecule.…”
Section: Thymocyte Negative Selectionmentioning
confidence: 99%
“…Transgenic expression of a dominant negative Nur77 protein, which can inhibit both Nur77 and Nor-1, does antagonize negative selection. 75,76 Therefore, it has been hypothesized that there may be redundancies between the family members. How Nur77 can induce apoptosis is still unclear, but one proposed mechanism is that upon TCR stimulation Nur77 is translocated from the nucleus to the mitochondria where it interacts with BCL-2 inducing a conformational change that converts BCL-2 into a proapoptotic molecule.…”
Section: Thymocyte Negative Selectionmentioning
confidence: 99%
“…Cell proliferation is initially widespread in the prospective canal region, but after canal formation it becomes restricted to two regions of the canal ( Fig. 2.7; Chang et al 1999;Ponnio et al 2002). The loss of Nor-1 affected the proliferation and continual growth of all three canals and ampullae.…”
Section: Development Of the Semicircular Canalsmentioning
confidence: 99%
“…Although the expression patterns of Netrin 1 and Nor-1 in the inner ear are similar (highest in the fusion plate region), loss of Nor-1 function does not affect canal resorption. In Nor-1 knockout mice, the canals and ampullae are smaller than in wildtype mice (Ponnio et al 2002). Cell proliferation is initially widespread in the prospective canal region, but after canal formation it becomes restricted to two regions of the canal ( Fig.…”
Section: Development Of the Semicircular Canalsmentioning
confidence: 99%
“…NOR1 is highly expressed in the central nervous system during embryonic development (21). Our studies using previously generated NOR1-deficient mice demonstrated that NOR1 plays a critical role in neuronal survival, axonal guidance, and is required for the continuous proliferative growth of the semicircular canals (22,23). In addition, experiments using overexpression of NOR1 revealed that constitutive NOR1 expression in thymocytes results in apoptosis (24).…”
mentioning
confidence: 98%